Evaluation of Safety and Antileishmanial Efficacy of Amine Functionalized Carbon-Based Composite Nanoparticle Appended With Amphotericin B: An in vitro and Preclinical Study - Gedda, Mallikarjuna Rao; Madhukar, Prasoon; Vishwakarma, Alok Kumar; Verma, Vimal; Kushwaha, Anurag Kumar; Yadagiri, Ganesh; Mudavath, Shyam Lal; Singh, Om Prakash; Srivastava, Onkar Nath; Sundar, Shyam (Frontiers in Chemistry, 2020)
Visceral Leishmaniasis (VL) has been a major health concern in the developing world, primarily affecting the impoverished people. It is caused by a protozoan parasite Leishmania donovani and is characterized by immune dysfunction that can cause VL patients to succumb to secondary infections. Several adverse side effects limit the current drug options; hence, the need of the hour is some drug options with high efficacy and no toxicity. To make targeted delivery of Amphotericin B, we have used amine-functionalized versions of carbon nanostructures, namely, f-CNT and f-Graphene (f-Grap). The result on f-Grap-AmB because of a much larger surface area was expected to be much better. However, the results on f-Grap-AmB obtained by us showed only marginal improvement (IC50 f-Grap-AmB; 0.0038±0.00119 µg/mL). This is in all likelihood due to the agglomeration effect of f-Grap-AmB, which is invariably obtained with graphene. To resolve this issue, we have synthesized Graphene-CNT composite (Graphene 70% and CNT 30% by weight). Here because CNT is dispersed in between graphene sheets, the agglomeration effect is avoided, and our study suggests that the f-Comp-AmB showed no toxicity against the murine J774A.1 macrophage cell line and did not induce any hepatic or renal toxicity in Swiss albino mice. The f-Comp-AmB also showed a remarkable elevation in the in vitro and in vivo antileishmanial efficacy in comparison to AmB and f-CNT-AmB or f-Grap-AmB in J774A.1 and Golden syrian hamsters respectively. Additionally, we have also observed that the percentage suppression of parasite replication in the spleen of the hamster was significantly higher in the f-Comp-AmB (97.79±0.2375) treated group in comparison with the AmB (85.66±1.164) treated hamster group. To conclude, f-Comp-AmB could be a safe and reliable therapeutic option over the other carbon-based nanoparticles (NPs), i.e., f-CNT-AmB, f-Grap-AmB, and conventional AmB.